THE SIGNIFICANCE OF ADENOID VEGETATIONS ON BREATHING, HEARING AND DEVELOPMENT OF THE MAXILLOFACIAL SYSTEM IN CHILDREN - Shamsiev Djakhangir Fazlitdinovich; Abdusamatova Iroda Ilkhamovna (Western European Studies, 2025)
This literature review analyzes the influence of adenoid vegetation (nasopharyngeal tonsil vegetation), a common otorhinolaryngological problem in children, on the development of respiration, hearing, and the maxillofacial skeleton. Based on the analysis of scientific literature, it has been shown that adenoids, as a result of blocking nasal breathing, lead to the habit of breathing through the mouth, disruption of sleep quality, and conditions accompanied by hypoxia. Also, due to compression of the opening of the Eustachian tube, fluid accumulation in the middle ear (exudative otitis) and hearing loss were detected. It is substantiated that pathological formation of the maxillofacial skeleton, i.e., the development of "adenoid face" syndrome, is possible due to oral respiration. Studies show the importance of early diagnosis and comprehensive assessment of adenoid vegetation in children. The article provides recommendations for reducing the consequences of the disease based on modern diagnostic and therapeutic approaches
Keywords: adenoid vegetation; respiratory distress; exudative otitis